Bioactive peptides grafted silicone dressings: A simple and specific method. (June 2017) - Pinese, Coline; Jebors, Said; Stoebner, Pierre Emmanuel; Humblot, Vincent; Verdié, Pascal; Causse, Léa; Garric, Xavier; Taillades, Hubert; Martinez, Jean; Mehdi, Ahmad; Subra, Gilles
Abstract: The need for bioactive dressings increases with the population aging and the prevalence of chronic diseases. In contrast, there are very few dressings on the market which are designed to display a chosen bioactivity. In this context, we investigated the surface-functionalization of silicone wound dressing with bioactive peptides. One of the challenges was to avoid multistep grafting reactions involving catalysts, solvents or toxic reagents, which are not suitable for the fabrication of medical devices at an industrial scale. In the other hand, a covalent bonding was necessary to avoid the loss of the biological effect by progressive removal of the peptide in biological fluids generated by the wound. To solve these limitations, we developed a strategy allowing an easy and direct functionalization of silicone. This strategy relies on hybrid silylated bioactive peptides, which chemoselectively react with plasma-activated silicone surfaces. We synthesized three hybrid peptides with wound healing properties, which were grafted on commercially available silicone dressings Cerederm ® and Mepitel ® . Grafted dressings were evaluated in vitro and enabled a quicker scare recovery and extracellular matrix deposition with human dermal fibroblasts. These results were confirmed by in vivo studies showing an enhanced wound-healing of the pig skin. By this simple method, we transformed inert dressing into bioactive dressing which showed properties of wound healing. Graphical abstract: Highlights: A simple method for silicone dressing functionalization with peptides is presented. The grafting proceeds in a single step, by incubation with a hybrid silylated peptide. Bioactive peptides promotes scare recovery on the skin of a pig.